Awareness of Polish society about complications and contraindications in teeth whitening - Kula, Łucja; Jaślar, Tomasz; Szmidla, Zuzanna; Mocny-Pachonska, Katarzyna (Journal of Education, Health and Sport, 2022)
Introduction and aim: Teeth whitening, which has a positive effect on the quality of life and the human psyche but is associated with side effects and contraindications, is becoming increasingly popular and widespread. The aim of the study was to collect and analyse data concerning the awareness of the Polish population of complications and contraindications to tooth whitening. Material and methods: A survey was conducted using a Google document among teeth whitening and non-whitening individuals. Link to the survey posted on various social groups. Results: People who whiten their teeth in a dental office are the group that showed the highest awareness about the side effects and contraindications of teeth whitening. People who do not whiten their teeth are more aware than people who whiten outside the dental surgery. The popularised slogans such as the possibility of tooth hypersensitivity, weakening of the enamel or the necessity to follow a "white diet" are known to each study group. The issues connected with the dentist’s office were the least popular - persons whitening their teeth outside the dentist’s office are not aware of the necessity to professionally clean their teeth before this procedure. None of the study groups have knowledge about the temporomandibular joint problem as a contraindication to teeth whitening. Conclusions: The Polish population shows an average knowledge of teeth whitening. The basic contraindications and complications are known to a broader group of respondents, but there are aspects of whitening about which the knowledge of respondents is low and requires popularisation. In addition, the survey indicates that more research is needed into the relationship between the temporomandibular joint and tooth whitening.